International Society of Sports Nutrition Position Stand: nutritional considerations for single-stage ultra-marathon training and racing - Nicholas B. Tiller; Justin D. Roberts; Liam Beasley; Shaun Chapman; Jorge M. Pinto; Lee Smith; Melanie Wiffin; Mark Russell; S. Andy Sparks; Lauren Duckworth; John O’Hara; Louise Sutton; et al. (Journal of the International Society of Sports Nutrition, 2019)
Background In this Position Statement, the International Society of Sports Nutrition (ISSN) provides an objective and critical review of the literature pertinent to nutritional considerations for training and racing in single-stage ultra-marathon. Recommendations for Training . i) Ultra-marathon runners should aim to meet the caloric demands of training by following an individualized and periodized strategy, comprising a varied, food-first approach; ii) Athletes should plan and implement their nutrition strategy with sufficient time to permit adaptations that enhance fat oxidative capacity; iii) The evidence overwhelmingly supports the inclusion of a moderate-to-high carbohydrate diet (i.e., ~ 60% of energy intake, 5–8 g·kg− 1·d− 1) to mitigate the negative effects of chronic, training-induced glycogen depletion; iv) Limiting carbohydrate intake before selected low-intensity sessions, and/or moderating daily carbohydrate intake, may enhance mitochondrial function and fat oxidative capacity. Nevertheless, this approach may compromise performance during high-intensity efforts; v) Protein intakes of ~ 1.6 g·kg− 1·d− 1 are necessary to maintain lean mass and support recovery from training, but amounts up to 2.5 g.kg− 1·d− 1 may be warranted during demanding training when calorie requirements are greater; Recommendations for Racing . vi) To attenuate caloric deficits, runners should aim to consume 150–400 Kcal·h− 1 (carbohydrate, 30–50 g·h− 1; protein, 5–10 g·h− 1) from a variety of calorie-dense foods. Consideration must be given to food palatability, individual tolerance, and the increased preference for savory foods in longer races; vii) Fluid volumes of 450–750 mL·h− 1 (~ 150–250 mL every 20 min) are recommended during racing. To minimize the likelihood of hyponatraemia, electrolytes (mainly sodium) may be needed in concentrations greater than that provided by most commercial products (i.e., > 575 mg·L− 1 sodium). Fluid and electrolyte requirements will be elevated when running in hot and/or humid conditions; viii) Evidence supports progressive gut-training and/or low-FODMAP diets (fermentable oligosaccharide, disaccharide, monosaccharide and polyol) to alleviate symptoms of gastrointestinal distress during racing; ix) The evidence in support of ketogenic diets and/or ketone esters to improve ultra-marathon performance is lacking, with further research warranted; x) Evidence supports the strategic use of caffeine to sustain performance in the latter stages of racing, particularly when sleep deprivation may compromise athlete safety.